Self-regualtion learning student of SMK N 1 Solok and implications in guidance and couneseling services - Yani Eka Putri; Zikra Zikra (Consilium, 2021)
This study aims to describe how the general picture of self-regulation learning is seen from the aspects of organizing and transforming (organizing and transforming), setting goals and planning (goal setting and planning), seeking information (seeking information), keeping records and keeping records. and monitoring), managing the environment (environment structuring), self-conseuences, repeating and remembering (rehearsing and memorizing), seeking social assistance, checking records (reviewing records). This research uses descriptive quantitative research. The population in this study were all students of SMK N 1 Solok, totaling 841 students and the sample in this study amounted to 222 students. Sampling in this study using stratifed random sampling technique. The instrument used in this study was a questionnaire about self-regulation learning with a Likert scale model. The data analysis technique used descriptive statistical techniques. From the research results it can be concluded that the self-regulation learning of SMK N 1 Solok students based on the following aspects: (1) self-evaluation is in the low category with a percentage of 74% (2) organizing and transforming is in the category low with a percentage of 67% (3) aspects of setting goals and planning (Goal Setting and Planning) are in the medium category with a percentage of 44% (4) seeking information (seeking information) are in the high category with a percentage of 48% (5) keeping records and keeping records and monitoring is in the high category with a percentage of 50% (6) the environmental structuring aspect is in the high category with a percentage of 42%.